'Taking a line for a walk': On improvisatory drawing. Issue 2 (1st December 2021) - Nemirovsky, Ricardo; Dibley, Tam
In this article we reflect on a line traced by Julia. Julia is an undergraduate student in a class that includes a project entitled 'Lives of Lines'. As part of the activities of this project, the students were asked to draw continuously for a minute with a white marker on a black page, without lifting the marker, and without trying to represent anything in particular. We analyse Julia's tracing of the line as a kind of improvisation ‐ the same type of improvising that occurs in conversations, music playing, hiking, dancing and countless other activities. We characterize the improviser as a daydreamer immersed in a reverie: an open field of reciprocating forces, desires, surprises and recollections playing themselves out as some of them encounter their way forward free to proceed, and others do not. The improviser becomes an arena in which body, hand, pen, paper, chair, other bodies, traces, words and sounds mutually displace and attract on their own.